Lontra longicaudis (Carnivora: Mustelidae: Lutrinae): a scientometric analysis - SIMIÃO, CAROLINA M.; MONTEIRO-FILHO, EMYGDIO L.A. (Anais da Academia Brasileira de Ciências, 2024)
A scientometric analysis of the Neotropical Otter is essential to establish the progress in studies with the species, in order to improve its conservation status. This study aimed to identify, categorize, and evaluate published scientific papers on Lontra longicaudis. Quantitative data was analyzed through absolute and relative frequencies, represented by tables and maps. The results showed that the publications on the Neotropical Otter increased since 1993 and have been primarily published in a specific journal (IUCN Otter Spec. Group Bull.) on the subfamily Lutrinae. Most authors reside in countries such as Brazil, Mexico, and Colombia, and publish predominantly in English. The majority of studies were conducted with free-living specimens, notably in the Brazilian state of Rio Grande do Sul and in Mexico. The most commonly used keywords match the most frequent subjects: "place of occurrence" and "diet". Despite the increase in publications, research on the Neotropical Otter is still largely limited to Brazil, Mexico, and sites near research institutions. Gaps on essential information for the species conservation, such as its biology, ecology, and behavior, were identified. The need for further studies on the Neotropical Otter in all the territory it inhabits is evident.